2021
DOI: 10.1007/s10926-021-10005-8
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Advice for Prevention and Rehabilitation of Low Back Pain- Same or Different? A Study on Device-Measured Physical Activity and Register-Based Sickness Absence

Abstract: Purpose We lack knowledge on whether the advice of “being physically active” should be the same for prevention and rehabilitation of low back pain (LBP). Sickness absence is a key outcome for LBP prevention and rehabilitation. We investigated the associations between physical activity and long-term sickness absence (LTSA) among employees with and without LBP. Methods Between 2011 and 2013, 925 Danish employees wore a Actigraph GTX3 accelerometer for 1–5 workdays to measure physical activity and reported LBP in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…These effects on several health-related aspects make PA suitable for minimizing disability, improving participation in physical and social activities, and promoting quality of life ( 12 ). Furthermore, PA as part of multidisciplinary biopsychosocial framework appears to contribute positively to sick leave days, being part of a successful return-to work strategy ( 13 ). Thus, PA combines both preventive and multisystemic effects with few adverse consequences and at little cost ( 12 ).…”
mentioning
confidence: 99%
“…These effects on several health-related aspects make PA suitable for minimizing disability, improving participation in physical and social activities, and promoting quality of life ( 12 ). Furthermore, PA as part of multidisciplinary biopsychosocial framework appears to contribute positively to sick leave days, being part of a successful return-to work strategy ( 13 ). Thus, PA combines both preventive and multisystemic effects with few adverse consequences and at little cost ( 12 ).…”
mentioning
confidence: 99%
“…Previous literature on occupational and household MVPA has usually reported unfavourable relationships with LBP 28 29. Similarly, a recent study that used CoDA and included LBP sufferers found that reallocating time to leisure-time MVPA was associated with a lower risk of long-term sickness absence, while reallocating time to occupational MVPA was associated with a higher risk 30. Given that MVPA in our study included all domains, it may be that unfavourable association between MVPA as part of work and LBP28–30 dominated over favourable association between leisure-time MVPA and LBP 12 27 28.…”
Section: Discussionmentioning
confidence: 97%
“…The secondary analyses in our study also seem to point in this direction, however, because sample sizes are too small to perform subgroup analyses, results must be interpreted cautiously. Additionally, although the reason is not yet understood, a distinction between work and leisure time (MV)PA seems relevant for LBP prevention and rehabilitation to reduce long term sickness absence risk (Gupta et al, 2021) In the literature on PA in CLBP, one of the leading theories is based on avoidance-persistence behaviours (Hasenbring and Verbunt, 2010). While there is some evidence for this in self-report based studies, this is not confirmed by monitoring activities during daily life with accelerometry (Huijnen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%